Thermal analysis of 8.5 MVA disk-type power transformer cooled by biodegradable ester oil working in ONAN mode by using advanced EMAG–CFD–CFD coupling - Stebel, Michal (2022)
Power transformers are the first devices used to transfer the electrical energy produced in power plants to the grid to supply the industrial and individual receivers with electricity. The heat generation in windings and core, being an effect of the power losses, is usually dissipated in large units by using mineral oils, which are harmful to the environment. Nowadays, the industry and global society seek environmentally-friendly alternatives. One of the most promising substitute for their high biodegradability, safety in operation, and favourable thermo-physical properties are natural ester oils. For this reason, a numerical study of 8.5 MVA disk-type power transformer cooled using conventional mineral oil and a commercially used rapeseed ester oil is presented in this paper. Moreover, due to different thermal behaviour of the considered oils, the comparison was made for the unit working in different seasons of hot and moderate climate zones (Argentina and Poland). In the numerical approach, electromagnetic (EMAG) and computational fluid dynamics (CFD) models were used for a detailed study of the selected device. In particular, a novel and very efficient EMAG–CFD–CFD coupling procedure was developed to assess the cooling of the large power transformer. Such a coupled computational procedure allowed for the detailed investigation of the power loss, oil flow characteristics, and temperatures with a satisfying computational effort. The results showed that the average windings temperatures are higher by 2–9 K when the ester oil is used, dependent on the ambient conditions. The hotspot temperature in the low voltage windings increased by up to 9 K and up to 18 K in the high voltage windings using ester oil. According to the results, the oil duct construction requires modification in the high voltage region for transformers cooled using mineral oil in cold climate conditions.